Methylated Septin 9 as a Promising Biomarker in the Diagnosis and Recurrence Monitoring of Colorectal Cancer. (2nd July 2022) - Lu, Pingxia; Zhu, Xianjin; Song, Yanfang; Luo, Yue; Lin, Junsheng; Zhang, Junrong; Cao, Yingping; Huang, Zhengyuan
Abstract : Purpose . The clinical utility of plasma methylated septin 9 ( mSEPT9 ) DNA in screening and recurrence monitoring for colorectal cancer (CRC) is highly promising. The present study was performed to determine the diagnostic value of mSEPT9 in CRC detection and recurrence monitoring in Chinese patients. Methods . Overall, 616 patients newly diagnosed with CRC and 122 individuals with no evidence of disease were recruited from October 1, 2019, to May 31, 2021, at Fujian Medical University Union Hospital. Plasma and serum samples were collected for analyzing mSEPT9, carcinoembryonic antigen (CEA), and carbohydrate antigen-19-9 (CA19-9). Data on clinicopathological characteristics were collected and analyzed. Sensitivity and specificity were calculated to evaluate the diagnostic potential of each marker; the receiver operating characteristic (ROC) curve was applied for the assessment of diagnostic value, and comparisons among mSEPT9, CEA, CA19-9, and their combination were assessed via ROC curves. Results . mSEPT9 achieved an overall sensitivity and specificity of 72.94% and 81.97%, respectively, with an area under the curve (AUC) value of 0.826, which were higher than those of CEA (sensitivity: 43.96%; specificity: 96.72%; AUC: 0.789) and CA19-9 (sensitivity: 14.99%; specificity: 96.61%; AUC: 0.590). The combination of mSEPT9, CEA, and CA19-9 further improved sensitivity, specificity, and AUC value (sensitivity: 78.43%; specificity: 86.07%; AUC: 0.878), respectively. Notably, the mSEPT9 positivity rate was significantly associated with TNM stage, T stage, N stage, tumor size, vascular invasion, and nerve invasion among patients with CRC. A 100% correlation was observed between the positive results of the mSEPT9 test and recurrence or metastasis in patients after therapeutic intervention. Conclusion . Our findings suggest that mSEPT9 may represent a potential biomarker for the diagnosis and prognosis of CRC compared with CEA and CA19-9. Postoperative mSEPT9 status may represent the first noninvasive marker of CRC recurrence or metastasis.